2003
DOI: 10.1086/368361
|View full text |Cite
|
Sign up to set email alerts
|

Serological Responses among Individuals in Areas Where Both Schistosomiasis and Malaria Are Endemic: Cross‐Reactivity betweenSchistosoma mansoniandPlasmodium falciparum

Abstract: We examined specific immunoglobulin G1 (IgG1) and IgG3 responses to Plasmodium falciparum schizont and Schistosoma mansoni egg and worm antigens in individuals from Kenya, Uganda, and the Sudan who had been exposed to malaria and schistosomiasis. A strong correlation between malaria- and schistosome-specific IgG3 responses was observed. This association appears to result from the presence of cross-reactive components of the 2 parasites that bind IgG3 antibodies, rather than to be mediated by immunological cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 43 publications
(59 reference statements)
4
64
1
Order By: Relevance
“…Another possible explanation for the contrasting results of these two studies is that the African population has a high prevalence of malaria, a protozoan infection that is known to cause hepatosplenomegaly and also to induce high levels of TNF-␣ (11). In fact, a more recent study from one of these groups of investigators (19), evaluating the serological response in the same population described in the previous study, confirmed that hepatosplenic patients had significantly higher levels of anti-Plasmodium falciparum antibodies compared to levels of nonhepatosplenic patients (20). Further studies are necessary to better clarify the cytokines involved in advanced stages of hepatosplenic schistosomiasis and the role of coinfections with malaria and other pathogens.…”
Section: Discussionmentioning
confidence: 62%
“…Another possible explanation for the contrasting results of these two studies is that the African population has a high prevalence of malaria, a protozoan infection that is known to cause hepatosplenomegaly and also to induce high levels of TNF-␣ (11). In fact, a more recent study from one of these groups of investigators (19), evaluating the serological response in the same population described in the previous study, confirmed that hepatosplenic patients had significantly higher levels of anti-Plasmodium falciparum antibodies compared to levels of nonhepatosplenic patients (20). Further studies are necessary to better clarify the cytokines involved in advanced stages of hepatosplenic schistosomiasis and the role of coinfections with malaria and other pathogens.…”
Section: Discussionmentioning
confidence: 62%
“…The prevalence of schistosomiasis may be lower in older adults, or there may be age-related changes in antibody responses that make crossreactivity less likely (29). Schistosoma-specific antibody responses in areas where schistosomiasis is endemic have been shown to be dependent on the age of the individual and the intensity of infection (28). In studies designed to investigate resistance to reinfection with S. mansoni in areas of endemicity after treatment, the levels of IgG2 against parasite egg polysaccharide antigens were found to be the highest in younger children and declined with age, whereas other responses, such as the IgE response against adult worm antigens, tended to rise with age (9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…An in-house test was also performed to determine the presence of heterophile antibody. The details of the IgG assays have been described previously (14,28). S. mansoni antigens were obtained from a Puerto Rican isolate of S. mansoni maintained in the outbred Tucks original strain of mice (Harlan United Kingdom Ltd., Bicester, United Kingdom) and albino freshwater snails (Biomphalaria glabrata) in Cambridge (11).…”
Section: Methodsmentioning
confidence: 99%
“…9,22,[27][28][29][30] As to the two antagonistic responses (Th1 and Th2) described in animals and humans, it has been established that the immune response caused by helminth infections is predominantly Th2, leading to a Th1 downregulation and to an exacerbation of Th2-dependent antibody response, which would accelerate the process of parasite clearance, and favor P. falciparum elimination with a better control of malaria parasite density. 22 A recent study on malaria-urinary schistosomiasis coinfection, conducted in Senegal, showed that children presenting moderate intensity of urinary schistosomiasis infection produced higher IgG1 and IgG3 responses to whole P. falciparum extracts than children not infected with urinary schistosomiasis.…”
mentioning
confidence: 99%